2017
DOI: 10.1186/s12905-017-0473-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the association between quality of life and depressive symptoms during postpartum period: a correlational study

Abstract: BackgroundThe onset of a major depressive episode is experienced by a large number of women in the weeks or months following delivery. Postpartum depression may deem those women experiencing it incapable of taking care for themselves, their family and their infants, while at the same time it could negatively affect their quality of life. The present study assessed the quality of life of a sample of mothers in Greece, in order to investigate the association between postpartum depression and quality of life (QoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
6
28
0
3
Order By: Relevance
“…Although the WHO recommends that the rates of CS do not exceed 10-15% of births, Greece is in the highest position worldwide [26], which makes Greek women more exposed to birthtrauma [27]. So far, there is no research study of PTSD disorders in Greek women, while the data is limited to other mental disorders of the postpartum period [28,29]. The purpose of this investigation is first to study the frequency of PTSD between two groups of women-EMCS and ELCS-in the 6th week postpartum and secondly, to determinethe risk factors and their degree of contribution to the development of specific postpartum disorders.…”
Section: Ptsd-ac In Greek Womenmentioning
confidence: 99%
“…Although the WHO recommends that the rates of CS do not exceed 10-15% of births, Greece is in the highest position worldwide [26], which makes Greek women more exposed to birthtrauma [27]. So far, there is no research study of PTSD disorders in Greek women, while the data is limited to other mental disorders of the postpartum period [28,29]. The purpose of this investigation is first to study the frequency of PTSD between two groups of women-EMCS and ELCS-in the 6th week postpartum and secondly, to determinethe risk factors and their degree of contribution to the development of specific postpartum disorders.…”
Section: Ptsd-ac In Greek Womenmentioning
confidence: 99%
“…The HRQOL in women during pregnancy and in different phases of the postpartum period has been studied [4,7,8,9,10,11]. The results of a systematic review with meta-analysis that included 18 studies concluded that the type of delivery was associated with the HRQOL of the woman in the postpartum period: women with vaginal delivery had better quality of life than women who gave birth by caesarean section [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, anxiety was detected as a predictive factor, among others [9]. The authors of a Greek study on 154 women detected an association between postpartum depression symptoms and mothers’ quality of life [11].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have shown that education levels do not affect depression scores [28,33], others have found that low education level of the mother is a risk factor for postpartum depression. As depression scores decrease, mothers' education level increases [37][38][39].…”
Section: Discussionmentioning
confidence: 99%